Pengembangan dan Pemanfaatan Website Desa Balewangi Kecamatan Cisurupan Kabupaten Garut - Kuswara, Hadiati; Fauzia, Fathia Alisha; Firmansyah, Firmansyah; Gusdiana, Ridian (Jurnal Media Pengabdian Komunikasi, 2023)
Abstract Balewangi Village, Cisurupan District, Garut Regency, one of the villages that is part of the overall Indonesian government structure, is required to follow national policies and strategies for e-government development. Village website as a strategic tool in realizing the effectiveness of Village Government administration; accelerate the improvement of village community welfare; accelerate improvements in the quality of public services; improving the quality of Village Government governance; and increase the village's competitiveness. The purpose of this service is to develop and utilize the Balewangi Village Website, Cisurupan District, Garut Regency. Observation, discussion and participation methods are widely used in this service activity. Balewangi Village has supporting facilities for building a village website, namely an internet network is available at the village government office. The service activities that have been carried out have succeeded in designing network-based information and communication technology by designing the Balewangi Village website which can be accessed via http://desabalewangi.com. The results of this service show the design of the Balewangi Village website, Cisurupan District, Garut Regency. The main page of the website displays the profile of Balewangi Village which is equipped with several important menus, namely Village Announcements, Latest News, Village Head Column, Village Map, Village Resident Opinions as well as information about developments in the Covid-19 pandemic through the Covid-19 Statistics menu. Keywords: Website; government; technology; communication, optimization. Abstrak  Desa Balewangi Kecamatan Cisurupan Kabupaten Garut, salah satu desa yang merupakan bagian dari keseluruhan struktur pemerintahan Indonesia, dituntut untuk  mengikuti kebijakan dan strategi nasional pengembangan e-government. Website desa sebagai sarana strategis dalam mewujudkan efektivitas penyelenggaraan Pemerintahan Desa; mempercepat peningkatan kesejahteraan masyarakat Desa; mempercepat peningkatan kualitas pelayanan publik; meningkatkan kualitas tata kelola Pemerintahan Desa; dan meningkatkan daya saing Desa. Tujuan pengabdian ini adalah untuk melakukan pengembangan dan pemanfaatan Website Desa Balewangi Kecamatan Cisurupan Kabupaten Garut. Metode observasi, diskusi dan partisipasi banyak digunakan dalam kegiatan pengabdian ini. Fasilitas pendukung untuk membagun website desa telah dimiliki Desa Balewangi yaitu telah tersedia jaringan internet di kantor pemerintahan desa. Kegiatan pengabdian yang telah dilakukan berhasil melakukan perancangan  teknologi informasi dan komunikasi berbasis jaringan dengan cara merancang website Desa Balewangi yang dapat diakses melalui http://desabalewangi.com. Hasil pengabdian ini menunjukkan terancangnya website Desa Balewangi Kecamatan Cisurupan, Kabupaten Garut. Halaman utama website menampilkan profil Desa Balewangi yang dilengkapi dengan beberapa menu penting, yaitu  Pengumuman Desa, Berita Terbaru, Kolom Kepala Desa, Peta Desa, Opini Warga Desa serta informasi tengtang perkembanyan pademi covid-19 melalui menu Statistik Covid-19.Kata-kata kunci: Website; Pemerintah; Teknologi; Komunikasi; Pengembangan.